Methylation status of leptin receptor gene promoter in obese children - Jakubek-Kipa, Katarzyna; Potocka, Natalia; Skrzypa, Marzena; Dembinski, Łukasz; Zawlik, Izabela; Mazur, Artur (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Obesity in children is a growing problem in many countries around the world. Molecular processes have been identified that may lead to epigenetic patterns contributing to obesity, such as DNA methylation in promoters of specific genes. The leptin receptor gene (LEPR) has been associated with obesity, and the aim of our study was to evaluate the methylation status of the LEPR promoter in the white blood cells (WBC) of 50 children with obesity. Leptin receptor gene promoter methylation was analysed using Combined Bisulfite Restriction Analysis (COBRA). In all patients, the LEPR promoter was found to be unmethylated. The results may indicate that methylation of CpG islands in the LEPR promoter is not associated with obesity in children.